Social perceptions of third-party consent and the reasonableness test of Illinois v. Rodriguez - Kagehiro, Dorothy K. (Journal of research in crime and delinquency, 1992)
The article examines the psycho legal assumptions regarding the notion of common authority that supports the recent United States Supreme Court third party ruling in Illinois versus Rodriguez. Social perceptions and attitudes have played a role in the case law on constitutional issues, and courts have considered empirical evidence in their determinations of what those social perceptions and attitudes are. The empirical evidence most commonly considered by the courts has been in the form of aggregate data or public opinion polls. Previous research indicates that close personal relations and territorial functioning within shared residences do not correspond with legal assumptions about individuals' privacy expectations and behaviors. Because these assumptions form part of the legal justification for warrant less searches, the discrepancies have serious implications for police practices and the scope of protection afforded to individual privacy under the Fourth Amendment. Courts' consideration of individuals' privacy interests occur in the context of balancing tests involving other important societal interests